1979
DOI: 10.1007/bf01732340
|View full text |Cite
|
Sign up to set email alerts
|

Two types of amino acid substitutions in protein evolution

Abstract: The frequency of amino acid substitutions, relative to the frequency expected by chance, decreases linearly with the increase in physico-chemical differences between amino acid pairs involved in a substitution. This correlation does not apply to abnormal human hemoglobins. Since abnormal hemoglobins mostly reflect the process of mutation rather than selection, the correlation manifest during protein evolution between substitution frequency and physico-chemical difference in amino acids can be attributed to nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
288
2
1

Year Published

1980
1980
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 442 publications
(300 citation statements)
references
References 21 publications
9
288
2
1
Order By: Relevance
“…In all of the segments of the coding regions, Ks is always larger than KA. Such a high evolutionary rate of synonymous substitution has also been found in other genes (13,(16)(17)(18)(19)(20)(21). Comparisons of Ks and KA between different domains reveal-the remarkable result that both KS and KA of the CHI domain are significantly smaller than the corresponding difference of the other domains.…”
Section: Methodssupporting
confidence: 55%
See 1 more Smart Citation
“…In all of the segments of the coding regions, Ks is always larger than KA. Such a high evolutionary rate of synonymous substitution has also been found in other genes (13,(16)(17)(18)(19)(20)(21). Comparisons of Ks and KA between different domains reveal-the remarkable result that both KS and KA of the CHI domain are significantly smaller than the corresponding difference of the other domains.…”
Section: Methodssupporting
confidence: 55%
“…We have evaluated the sequence divergence of the coding region by measuring two distinct types of substitutions: one leading to amino acid change and the other leading to synonymous change (13). Obviously, the former is under the influence of selective constraints at both protein and RNA levels and the latter is under the influence of selective constraint at the RNA level alone.…”
mentioning
confidence: 99%
“…It has been suggested that positive selection tends to operate on the more conservative changes (19), whereas others argued that it works more often on the radical ones (20,21). There are two commonly used indices for the physicochemical differences between amino acids: Grantham's distance, which takes into account the volume, polarity, and carbon composition of the side chain of each amino acid (22), and Miyata's distance, which measures volume and polarity (23). Conservative changes have smaller distances than radical ones by either measure.…”
Section: Contrasting Divergence and Polymorphism For The 75 Elementarymentioning
confidence: 99%
“…In contrast, we find that negative selection among nonsynonymous polymorphisms is widespread, and that the strength of negative selection on nonsynonymous sites is predicted by several measures of amino acid exchangeability, i.e., ''radical'' amino acid mutations tend to be more deleterious than ''conservative'' changes. Several methods have been proposed for quantifying the impact of different types of amino acid changes on protein structure and function (16)(17)(18)(19)(20)(21)(22); examples of different criteria that are used include physicochemical properties of the change, phylogenetic patterns of substitution, and experimental measures of the effect of different substitutions on protein structure and activity. However, the relationship between these measures and evolutionary fitness has not been fully explored.…”
mentioning
confidence: 99%